The correlations of method between the first and the subsequent childbirth at PKU Muhammadiyah Yogyakarta hospital in 2016 - Lianawati Lianawati; Menik Sri Daryanti (Universitas 'Aisyiyah Yogyakarta, 2019)
The birth of elective Caesarean Sectio leads to a 3-fold risk than the risk of vaginal birth, whereas emergency Sectio Caesarean birth causes a 9-fold risk than the risk of vaginal delivery. This research uses analytic observational design. The data retrieval uses a retrospective time approach. The sample in this research is taken with purposive sampling technique (January 1 st 2016 to December 31 th 2016), were 195 patients. This study, using secondary data. Data analysis used Chi Square. With significance level 0,05 obtained result of P Value equal to 0,000 (P Value 0.05) and value of closeness (Phi) equal to 0,612. Therefore it can be concluded there is a relationship between the first labor with the next labor at PKU Muhammadiyah Yogyakarta Hospital in 2016 with the strong relationship.